A review of the role of nature-based solutions in mitigating food insecurity in Africa - Solomon Asamoah; Henry Mensah; Eric Kwame Simpeh; Eric Oduro-Ofori; Sandra Serwaa Boateng; Sarah Boateng; Listowel Koda Frimpong; Priscilla Okyere (Green Technologies and Sustainability)
The study explores the role of nature-based solutions in addressing food insecurity in Africa, with the broader goal of advancing knowledge in this field. This study utilized a scoping review to identify peer-reviewed literature and VOSviewer for bibliometric analysis. Abductive reasoning was employed to analyze the collected data, which were then subjected to thematic analysis using an iterative read-and-review procedure. The study identified agroforestry, permaculture practices, urban agriculture and rooftop gardens, wetland restoration, cover cropping and crop rotation, aquaponics, eco-friendly pest control, and community-based forest management as components of nature-based solutions that can help address food insecurity. However, despite the growing interest in nature-based solutions as a potential solution, a comprehensive understanding of its efficacy, challenges, and implications for addressing food insecurity in Africa remains limited. Existing research has primarily focused on case studies and localized interventions, with a gap in synthesizing broader trends, identifying key research areas, and exploring intersectionality.